THE MAKING OF A MAGIC DICE GAME TO LEARN ENGLISH VOCABULARY FOR ELEMENTARY SCHOOL STUDENTS - Nurazlinda Nurazlinda; Safra Apriani Zahraa (INOVISH JOURNAL, 2017)
Abstract: English is widely used over the world. In English, there are some aspects that must be mastered as well namely grammar, pronounciation, and vocabulary. Vocabulary is one of aspects that must be mastered, because before we are able to speak, write, and listen, the vocabulary is the first thing we have to master before grammar. However, in learning vocabulary, the students still face difficulties. For example, they always have problems in knowing, memorizing, and understanding the new words. Therefore, the media that used in learning will surely help the students understand the lesson well. Besides, they can also learn English in a more effective and interesting way. The main purpose of this Â is making a Magic Dice game which can be used as an alternative in learning vocabulary, for students in elementary school level. This project produced a set of Magic Dice game consisting of six sets of question cards related to part of body, vegetables, fruits, nouns, adjectives, colors, animals and profession, a set of shocking cards, and a big dice. This game can be used in classes during the learning-teaching process. It can helps the students in knowing and understanding the new words of vocabulary. By using this game, the students more interested in learning vocabulary.Â Keywords: Magic Dice game, Learning Vocabulary